Planning the Scaling of Rice-Based Innovations through the Agricultural Information Services: Workshop proceedings report - International Rice Research Institute (International Rice Research Institute, 2025)
The International Rice Research Institute (IRRI), in collaboration with the Agricultural Information System (AIS), organized a planning workshop on 19 May 2025 in Dhaka to explore pathways for scaling rice-based innovations in Bangladesh. The workshop focused on aligning IRRI’s climate-smart and sustainable rice innovations with AIS’s national information dissemination platforms to enhance outreach of rice-based innovations. Key discussions addressed innovation scaling models, agronomic and water management solutions for coastal polder zones, and the use of digital, print, and broadcast media for knowledge sharing. Participants emphasized the development of a joint scaling roadmap, and formalizing collaboration through a memorandum of understanding. The workshop laid the groundwork for a strategic partnership to support sustainable rice-based agri-food systems and national food security goals